Chalcogenylation of Naphthalene Derivatives Catalyzed by Iron(III) Chloride and Potassium Iodide - Seckler, Diego; da Luz, Eduardo Q. da; Silvério, Gabriel L.; Badshah, Gul; Lima, David B.; Abreu, Emerson A.; Albach, Breidi; Ribeiro, Ronny R.; Rampon, Daniel S. (Synlett, 2021)
We have developed an efficient chalcogenylation of electron-rich naphthalene derivatives catalyzed by FeCl3 and KI. The methodology provides access to several nonsymmetrical diorganoyl chalcogenides (S, Se) by selective C1 chalcogenylation of 2-naphthols or 2-naphthylamines using simple and cheap catalysts. Several control experiments supported the hypothesis that a redox reaction between Fe(III) and KI produces I2, which catalyzed the chalcogenylation.
Keywords: iron catalysis; potassium iodide catalysis; sulfanylation; selenylation; naphthylamines; naphthols